THE RISK OF PHALLOCENTRISM IN MASCULINITIES STUDIES: HOW A REVISION OF THE CONCEPT OF PATRIARCHY MAY HELP - Macleod, Catriona (PINS-Psychology in Society, 2025)
In this article I critique South African work on masculinities through a fine grained reading of Morrell’s introductions to three texts. While this work appears, on first reading, to contribute to pro-feminist theorising, I argue that it inadvertently falls into a phallocentric trap. This is achieved in three ways: firstly, and most crudely, through conflating women and men into a singular, universal model that is in reality the masculine appearing as the universal; secondly, and more subtly, through concentrating almost exclusively on men and masculinities, thereby marginalising women (again); and thirdly, through constructing multiplicities of masculinities – this allows men to resist hegemonic masculinity, but never undo masculinity itself. In this way, the possibility of deconstructing the feminine/masculine binary recedes and the concept of patriarchy gets sidelined. I argue for a reinsertion of the notion of patriarchy into our study of gender, but also that the very notion of patriarchy needs revision in order to accommodate the multiple fissures that occur between men.